2002
DOI: 10.1046/j.1464-5491.2002.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Awareness Training in Dutch Type 1 diabetes patients. Short‐term evaluation of individual and group training

Abstract: The effects of BGAT were smaller than expected. Possible reasons for this negative outcome may be the adapted version of BGAT (shorter in duration), a lack of statistical power, or a difference between American and European samples in their reaction to BGAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 14 publications
0
43
0
1
Order By: Relevance
“…Broers et al 11 hypothesized that BGAT administered individually would be more effective than when delivered in the traditional group format. There was no difference between individually and groupadministered BGAT- 19 demonstrated that the Dutch BGAT-1 significantly improved recognition of hypoglycemic episodes, improved decisions not to drive during hypoglycemia, improved decisions to raise low blood glucose, and significantly reduced both the occurrence of severe hypoglycemic episodes and vehicular collisions.…”
Section: Blood Glucose Awareness Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Broers et al 11 hypothesized that BGAT administered individually would be more effective than when delivered in the traditional group format. There was no difference between individually and groupadministered BGAT- 19 demonstrated that the Dutch BGAT-1 significantly improved recognition of hypoglycemic episodes, improved decisions not to drive during hypoglycemia, improved decisions to raise low blood glucose, and significantly reduced both the occurrence of severe hypoglycemic episodes and vehicular collisions.…”
Section: Blood Glucose Awareness Trainingmentioning
confidence: 99%
“…Unit 8 summarizes what has been learned from the previous 7 weeks of training and promotes relapse prevention. The manual for the second version of BGAT (BGAT-2) is written in English and has also been translated into German, 10 Dutch, 11 and Japanese. The first randomized clinical trial by Cox et al 13 investigated whether the first version of BGAT-1 improved accuracy of blood glucose estimates.…”
Section: Blood Glucose Awareness Trainingmentioning
confidence: 99%
“…43 Since then, BGAT, has undergone revision and adapted for use in various countries, showing sustained benefits in reducing SH rates, and improving hypoglycemia awareness through the ability to detect low BG values, without affecting glycemic control. 44,45 BGAT functions on the premise that systematic feedback provides the information needed to make adjustments in diabetes management to improve self-regulation. BGAT can be delivered through the internet, as another way of using technology to reduce hypoglycemia.…”
Section: Better Predictionmentioning
confidence: 99%
“…The device has been successfully used by health professionals when documenting patient data and using printed data in decision making [5,6,7], telementoring surgical procedures [8], securing patients' identity at blood sampling and transfusion procedures [9], following patients' blood glucose level [10], measuring rapidly and easily blood pressure, pulse rate, temperature, and oxygen saturation via health monitoring sensors connected to the handheld computer [11], and in counselling patients about their symptoms [12]. Hand-held computers have also been used to document clinical and educational activities and in medical student education, daily training, clinical practice and research [13,14,15].…”
Section: Introductionmentioning
confidence: 99%